Estudio del efecto de diferentes fuentes de fibra soluble sobre la integridad de la mucosa intestinal en cuyes (Cavia porcellus) en el post destete - Pacheco Ludeña, Jorge Luis (2025)
The inclusion of soluble fiber sources in the diet of food animals such as guinea pigs (Cavia porcellus) is based on the change that fiber makes in the small intestine of some animals, influencing the absorption of nutrients and the integrity and functionality of the mucosa. Therefore, this study evaluated the effects of different sources of soluble fiber on the integrity of the intestinal mucosa in guinea pigs (Cavia porcellus) in the post-weaning period. For this purpose, 30 weaned guinea pigs of 15 days of age of both genders, type A1, were fed 3 treatments based on soluble fibers, the first group with alfalfa, the second with pectins, and the third with citrus pulp. After 10 days of treatment, they were sacrificed to collect the corresponding samples from the middle region of the small intestine (jejunum) and fixed in 10% formalin. The samples were processed with PAS (Periodic Acid-Schiff) stain and the villus length, crypt depth, villus length/crypt depth ratio, villus epithelium height, and muscular tunica width were analyzed. As a result, none of the variables showed significant differences (P ≥ 0.1003) after feeding the different diets; however, a trend was identified concerning the height of the epithelium with the feed containing pectin as a source of soluble fiber. Therefore, it was concluded that no significant effects were determined with the different sources of soluble fiber on the integrity of the intestinal mucosa in guinea pigs (Cavia porcellus) in the post-weaning period.